MR elastography and diffusion‐weighted imaging of ex vivo prostate cancer: quantitative comparison to histopathology. (10th November 2014) - Sahebjavaher, Ramin S.; Nir, Guy; Gagnon, Louis O.; Ischia, Joseph; Jones, Edward C.; Chang, Silvia D.; Yung, Andrew; Honarvar, Mohammad; Fazli, Ladan; Goldenberg, S. Larry; Rohling, Robert; Sinkus, Ralph; et al.
<x xml:space="preserve">Abstract</x> The purpose of this work was (1) to develop a magnetic resonance elastography (MRE) system for imaging of the ex vivo human prostate and (2) to assess the diagnostic power of mono‐frequency and multi‐frequency MRE and diffusion weighted imaging (DWI) alone and combined as correlated with histopathology in a patient study. An electromagnetic driver was designed specifically for MRE studies in small‐bore MR scanners. Ex vivo prostate specimens (post‐fixation) of 14 patients who underwent radical prostatectomy were imaged with MRE at 7 T (nine cases had DWI). In six patients, the MRE examination was performed at three frequencies (600, 800, 1000 Hz) to extract the power‐law exponent Gamma. The images were registered to wholemount pathology slides marked with the Gleason score. The areas under the receiver‐operator‐characteristic curves (AUC) were calculated. The methods were validated in a phantom study and it was demonstrated that (i) the driver does not interfere with the acquisition process and (ii) the driver can generate amplitudes greater than 100 µm for frequencies less than 1 kHz. In the quantitative study, cancerous tissue with Gleason score at least 3 + 3 was distinguished from normal tissue in the peripheral zone (PZ) with an average AUC of 0.75 (Gd), 0.75 (Gl), 0.70 (Gamma‐Gd), 0.68 (apparent diffusion coefficient, ADC), and 0.82 (Gd + Gl + ADC). The differentiation between PZ and central gland was modest for Gd (p < 0.07), Gl (p < 0.06) but not significant for Gamma (p < 0.2). A correlation of 0.4 kPa/h was found between the fixation time of the prostate specimen and the stiffness of the tissue, which could affect the diagnostic power results. DWI and MRE may provide complementary information; in fact MRE performed better than ADC in distinguishing normal from cancerous tissue in some cases. Multi‐frequency (Gamma) analysis did not appear to improve the results. However, in light of the effect of tissue fixation, the clinical implication of our results may be inconclusive and more experiments are needed. Copyright © 2014 John Wiley & Sons, Ltd.